Use of statin for the primary prevention of cardiovascular outcomes in elderly patients: A propensity-matched cohort study. (July 2021) - Cho, Yongin; Jeong, Yujin; Seo, Da Hea; Ahn, Seong Hee; Hong, Seongbin; Suh, Young Ju; Kim, So Hun
Abstract: Background and aims: Herein, we investigate whether statin treatment as primary prevention reduces cardiovascular outcomes in elderly Asian patients. Methods: Data were obtained from the Korean National Health Insurance Service-Senior Cohort database (n = 558, 147). A total of 81, 729 elderly patients (≥75 years) without clinically recognized atherosclerotic cardiovascular disease (CVD) were included. The patients who did not have a history of statin use in year 2003 were followed from January 2004 to the end of 2012. New statin users (n = 3670) were matched on the basis of the propensity score in a 1:2 ratio with non-users. Incidences of myocardial infarction, ischemic stroke, and death from CVD were compared using the Cox proportional hazards model. Results: The risk of cardiovascular death was significantly reduced in the statin treatment group compared with the non-user group (hazard ratio [HR] 0.34, 95% confidence interval [CI] 0.29 to 0.40; p < 0.001). This effect was observed in both patient groups with and without diabetes. In patients with diabetes, the HR for statin use was 0.85 (95% CI 0.55 to 1.33) for myocardial infarction and 0.75 (95% CI 0.60 to 0.93) for ischemic stroke. In participants without diabetes, the HR of statin use was 0.95 (95% CI 0.73 to 1.24) for myocardial infarction and 1.13 (95% CI 1.01 to 1.26) for ischemic stroke. The presence of hypertension was also a significant factor in the prevention of ischemic stroke by statin treatment. Conclusions: In elderly patients without clinically recognized atherosclerotic CVD, the risk of cardiovascular mortality was significantly reduced with statin treatment than with non-users. In participants with type 2 diabetes, statin treatment was associated with a reduction in ischemic stroke. Graphical abstract: Image 1 Highlights: The long term effects of statin therapy are uncertain, especially in elderly Asians. The risk ofcardiovascular mortality was significantly reduced with statin treatment. Statin treatment reduced the risk of ischemic stroke in elderly patients with T2DM.